Association between sleep quality and duration during pregnancy and risk of gestational diabetes: A systematic review and meta-analysis - Minhua Jiang; Renhong Sui; Xiaoqing Wu (Gynecological Endocrinology)
Objective Gestational diabetes mellitus (GDM) is associated with several adverse maternal and neonatal outcomes. Previous studies reported a link between altered sleep and risk of GDM. This systematic review aims to collate evidence on the association between impaired sleep quality and duration, and the risk of GDM.Methods PubMed, Embase, Web of Science, and Scopus databases were searched up to January 20, 2024. Studies reporting the association between impaired sleep quality and duration and risk of GDM were included. Sleep quality was assessed by the Pittsburgh Sleep Quality Index (PSQI). Random-effects meta-analysis was performed, and the results were reported as hazard ratio (HR) with 95% confidence interval (CI).Results 19 studies were included. Meta-analysis revealed a significant increase in the risk of GDM in pregnant women with poor sleep quality (i.e. <5 PSQI) (HR: 1.50, 95% CI: 1.26 − 1.78, p < .001). Sleep duration of <7 h (HR: 1.56, 95% CI.: 1.20 − 2.01, p < .001), and >8 h (HR: 2.32, 95% CI.: 1.19 − 4.50, p = .01) were also associated with a significantly higher incidence of GDM.Conclusion Sleep quality and duration emerge as critical risk factors of GDM. Healthcare practitioners should consider targeted interventions to improve sleep hygiene as a potential measure for GDM prevention.